2002
DOI: 10.1016/s0928-8244(02)00279-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the protective efficacy of an oprF DNA vaccine against Pseudomonas aeruginosa

Abstract: The outer membrane protein F gene (oprF) of Pseudomonas aeruginosa was recently shown by us to protect mice from P. aeruginosa chronic pulmonary infection when used as a DNA vaccine administered by three biolistic (gene gun) intradermal inoculations given at 2-week intervals. In the present study, we used two different strategies to improve the protective efficacy of the DNA vaccine. In the first strategy, mice were primed with two biolistic intradermal inoculations with the oprF vaccine and then were given a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Specificity of serum IgG was analyzed by using immunoblots of flagella prepared from PAO1 and PAK as described previously (29,33). After separation by SDS-PAGE, samples were blotted on polyvinylidene difluoride membranes.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Specificity of serum IgG was analyzed by using immunoblots of flagella prepared from PAO1 and PAK as described previously (29,33). After separation by SDS-PAGE, samples were blotted on polyvinylidene difluoride membranes.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Immunization with recombinant OprF has been shown to generate protective immune responses, and recombinant OprF is being tested as a vaccine candidate against infections with P. aeruginosa in animals and humans (22)(23)(24)(25)(26)(27)(28). Genetic immunization with DNA encoding an OprF/OprI hybrid via a gene gun in mice resulted in humoral immunity against P. aeruginosa (29). Various immunogenic peptides have been identified in the outer loops of OprF, among them the B cell epitopes TDAYNQKLSERRAN (peptide 9, identical to Epi6) and NATAE-GRAINRRVE (peptide 10, identical to Epi8) (21).…”
Section: Figurementioning
confidence: 99%
“…OprF has been shown to be immunogenic in laboratory animals and humans, and the sequence of OprF suggests that there are several extracellular loops that serve as good B cell epitopes ( Figure 1) (21)(22)(23)(24)(25)(26)(27)(28)(29). The Ad hexon is the most abundant immunogenic of the Ad capsid proteins (30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…125,126 Many of the initial vaccination studies demonstrated that immunization with either OprF or OprI as immunogens elicits cross-reactive, opsonizing and protective antibodies in animal models or humans. [127][128][129][130][131][132][133][134] To enhance synergistic immunogenicity, a recombinant hybrid vaccine using immunogenic epitopes from OprF and OprI was developed. Active or passive immunization with this OprF-OprI vaccine was protective against systemic P. aeruginosa infection in various animal models.…”
Section: Outer Membrane Proteinsmentioning
confidence: 99%
“…151 OprI was demonstrated to adhere to the mucosal surfaces of the respiratory and intestinal tract and may so act as a mucosal carrier to facilitate antigen delivery to antigenpresenting cells. 152 In addition to conventionally extracted or recombinant protein preparations, Opr have been successfully tested in several other formulations including DNA vaccines, 129,130 peptide vaccine, 153 viral vectors, 154-159 dendritic cell-pulsed, 160 or heterologously expressed in bacterial vectors. 70 Furthermore, many of the chimeric vaccines include OprF/OprI as their critical component.…”
Section: Type III Secretion System Extracellular Toxins and Proteasesmentioning
confidence: 99%